2016
DOI: 10.1039/c5gc02612a
|View full text |Cite
|
Sign up to set email alerts
|

Methyl NFSI: atom-economical alternative to NFSI shows higher fluorination reactivity under Lewis acid-catalysis and non-catalysis

Abstract: Me-NFSI is more effective for the fluorination of active methines under Lewis acid-catalysis and non-catalysis than NFSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…After a break of a decade, in 2013, chiral dicationic DABCO-based N -F reagents 36-5 and chiral N -fluorobinaphthyldisulfonimides 37-2 were reported by Gouverneur [ 107 ] and by Shibata, Ma, and Cahard [ 108 ], respectively. In 2016, Shibata reported N -fluoromethanesulfonimide (Me-NFSI) as a high atom-economy reagent [ 111 ] and Gouverneur and Cvingroš reported a novel N -F reagent 39-3 derived from the ethylene-bridged Tröger base [ 113 ]. More recently, Zipse and Renaud in 2018, disclosed N -fluoro- N -aryl-arenesulfonamides (NFAS) as radical fluorinating agents [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After a break of a decade, in 2013, chiral dicationic DABCO-based N -F reagents 36-5 and chiral N -fluorobinaphthyldisulfonimides 37-2 were reported by Gouverneur [ 107 ] and by Shibata, Ma, and Cahard [ 108 ], respectively. In 2016, Shibata reported N -fluoromethanesulfonimide (Me-NFSI) as a high atom-economy reagent [ 111 ] and Gouverneur and Cvingroš reported a novel N -F reagent 39-3 derived from the ethylene-bridged Tröger base [ 113 ]. More recently, Zipse and Renaud in 2018, disclosed N -fluoro- N -aryl-arenesulfonamides (NFAS) as radical fluorinating agents [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Shibata et al reported the synthesis and reactivity of N -fluoromethanesulfonimide (Me-NFSI, 38-2 ) [ 111 ]. Me-NFSI was first reported in a patent in 1994 [ 112 ], however, the reported fluorinations were vague.…”
Section: Reviewmentioning
confidence: 99%
“…For instance, Shibata and co‐workers reported that NFBSI [ N ‐fluoro‐(3,5‐di‐ tert ‐butyl‐4‐methoxy)benzenesulfonimide] as a sterically more demanding NFSI derivative allows the cinchona alkaloid‐catalyzed fluorination of silyl enol ethers to be performed with higher enantioselectivity than in the case of NFSI itself, although the steric hindrance of the former reagent results in decreased reactivity [15] . The above authors also disclosed that the use of a sterically less demanding NFSI derivative (Me‐NFSI) improves reactivity in the Lewis acid‐catalyzed fluorination of β‐keto esters, oxindoles, and malonates [16] . Yang and co‐workers independently reported that in the case of oxindole fluorination, enantioselectivity and reactivity can be increased through the use of structure‐micro‐tuned NFSIs with different substituents on benzene rings [17]…”
Section: Introductionmentioning
confidence: 99%
“…For example, as presented in Figure 1, 1-chloromethyl-4-fluoro-1,4-diazoniabicyclo [2.2.2]octane bis(tetrafluoroborate) (1), introduced by Professor E. Banks [72], also known as Selectfluor, is one of the best reagents used as a source of "electrophilic fluorine". Other reagents, developed by Professor N. Shibata [73][74][75][76], are N-fluoro-N-(methylsulfonyl)methanesulfonamide (Me-NFSI) (2), 3,5-di-tert-butyl-N-((3,5-di-tert-butyl-4-methoxyphenyl)sulfonyl)-N-fluoro-4-methoxybenzenesulfonamide (NFBSI) (3) and axially chiral NFSIs (4), which can be used for enantioselective fluorination [77]. All these reagents are shelf-stable, easy to handle and operationally convenient to use for various synthetic applications [78][79][80][81].…”
Section: Introductionmentioning
confidence: 99%